Obtenção de nanopartículas lipídicas sólidas contendo (-)-Terpinen-4-Ol - Angelieri, Natália Ferri [UNESP] (2013)
The search for new drugs, mostly derived from medicinal plants has been studied in search of a more effective treatment for cancer. MACCARI (2009) proved that the drug (-)-terpinen-4-ol (TERP) has activity against tumor cells trough an in vitro study of antiproliferative activity. During the last decades nanoparticulate carrier systems have been the subject of research for the encapsulation of drugs used in cancer therapy. It is known that drugs with low aqueous solubility, as the TERP, when encapsulated in nanoparticle systems, tend to decrease their degradation, allow control release, alter biodistribution, even allowing targets organ and tissue are achieved. The objective of this work was the development and characterization of solid lipid nanoparticles (NLS) containing TERP. The NLS was obtained by high pressure homogenization (HAP) technique which has been standardized for the passage of the sample for 10 cycles at a pressure of 7.200psi. The lipid concentration which was the glyceril monostearate (GMS) was pre-stipulated to 5% and the proportion of surfactant consisting of 1:1 ratio of hydrogenated soy phosphatidilcholine (FSH) and poloxamer 188 (P-188) in surfactant concentration of 3%. The preliminary stability study of the TERP in front of the heating at 70 ° C by TG and DSC analysis and also the quantification proved that the drug can be incorporated using the HAP technique. The NLS 2,5 and NLS 5 showed particle size in the nanometer range while the NLS10, NLS 15 and NLS 20 showed particles in nano and micrometer size. The TG and DSC analysis showed that at lower concentrations, the TERP interacts with the system and is found in large quantity inside the lipid matrix which promoted a prolonged release for NLS 2,5 and NLS 5 system, while NLS 20 had a high burst effect, releasing about 80% of the total amount of TERP present in the formulation. Morphological characterization confirmed the results obtained by the light scattering ...